Journal publication and case report book 2005-2009 - Ali Hassan, Abdullah Alashw Al (2008)
A 34-year-old Malay man presented with mild reduced vision RE associated with foreign body sensation, redness and tearing. The problem was started one week back with RE redness, irritation and tearing. Two days later he experienced mild reduced of vision and he noted white opacity over right cornea. He was using eye drops given by a pharmacist however the condition getting worse. The patient did not report any known ocular traumatic injury and there was no history of wearing contact lens. There was no history of previous similar attack and no medical illness had been known. Social history revealed that he is working as lorry driver for about 10 years. Ocular examination revealed best corrected visual acuity of 6/18 OD and 6/6 OS. Right eye showed marked conjunctival injection, presence of para-central corneal ulcer measuring 3x2.8 mm. The margin was slightly elevated and ill defined. There was also deep stromal inflammatory infiltration (figure 1 ). Staining the lesion with fluorescein stain revealed epithelial defect (figure}). Occasional cells were noted in the anterior chamber. There was no hypopyon. The intraocular pressure was 15 mm Hg. The lens was clear and fundus examination was uneventful. General physical examination and systemic work-up were normal.